The Implementation of Pancasila and Civic Education Building A Harmonious Life in Bhinneka Tunggal Ika - Tjandra, Miki; Ginting, Seriwati; ., Abdul Rahmat (KnE Social Sciences, 2023)
Currently Pancasila and its values are being ignored. There are indications to reject Pancasila after the reformation. Nationalism as the unifier in diversity began to evaporate. Various problems related to ideological, political, legal, economic, religious issues came to the surface. All of this needs to be considered as a threat to national harmony. What has happened to the Dayak and Madura tribes is one proof that the problem of ethnocentrism exists and will arise if we are not aware of it. The role of civic education, especially at the university level, needs to be studied whether it still functions as social control or only as a formality. The method in this study uses sequential explanatory mixed methods. Through this research, civic education learning will be traced and analyzed more in-depth at the university level in terms of the material provided, whether it is still one-way in nature, or it is applicable related to real phenomena in students, by focusing on their life experiences. Keywords: civic education, nationalism, Pancasila, social control, university